Achieving a more inclusive financial system: What does the MENA region need? A sensitivity analysis for GCC and non-GCC countries - Abdelaziz Hakimi; Hichem Saidi; Lamia Adili (Economies, 2025)
Achieving a more inclusive financial system is crucial to unlocking economic opportunities, reducing inequality, and ensuring that no person will be excluded from access and usage of financial and banking services. Even if financial services are widely available in some areas, others, especially in developing nations, have low levels of financial inclusion and continue to confront obstacles that restrict economic growth and participation. This study examines the key factors influencing financial inclusion by analyzing 74 banks across 10 MENA countries from 2010 to 2021. It performs the System Generalized Method of Moments (SGMM) technique as an empirical approach. The results indicate that economic growth, education, infrastructure, and institutional quality have a significant impact on improving the level of financial inclusion in the MENA region. The results of the sensitivity analysis reveal that, in either GCC or non-GCC countries, key determinants include education, infrastructure, institutional quality, and GDP growth, leading to a more inclusive financial system.
Keywords: 330; financial inclusion; access; usage; MENA; GCC; non-GCC; SGMM